Personality Traits of Moira in Nora Robert’s Valley of Silence Novel - Radhiyatus Sara Hidayah; Anggun Purnomo Arbi (PGRI Provinsi Jawa Timur, 2022)
Character, in novel, plays crucial role in the development of the story. People often do not understand how the characters of the movie play their roles. Thus, this research aimed to analyze the personality trait of the main character in Nora Roberts’ Valley of Silence Novel 2006 and also the characterization method to reveal the main character’s traits. In classifying and analyzing data, the researchers applied the descriptive qualitative method as the data were not in the form of statistical data. The data were taken from the scripts of Nora Roberts’ Valley of Silence Novel (2006). To analyze personality trait including extraversion, neuroticism, openness, conscientiousness, and agreeableness, the theories of personality trait by McCrae and Costa in Gerald, et, al. (2003) were used, and the theories of characterization by Shlomith Reymon Kennan (2005) were used in order to analyze characterization. To validate the data, the triangulation technique was used. The result of this research showed that Moira as the main character of Valley of Silence Novel has Extraversion as the type personality trait. It is because her behavior is same with the facet of extraversion. Actually her personality trait can be changed sometimes, because of some particular event, but her personality trait is dominant in extraversion. The author describes Moira by using indirect presentation and speech as the way to represent the main character.